RISK IN PUBLIC PASSENGER TRANSPORT (Perner's Contacts, 2013)
The paper deals with an analysis of risks which affect reasonable profit. These risks are divided into two basic groups: cost risk and income risk. The paper describes ways of dividing risks between contractual sides. In the last part, the relationship which expresses the functionality between reasonable profit and risk in public passenger transport is discussed.
Keywords: ordering; risk; transport; serviceability